Interiority Across the Scales - Atmodiwirjo, Paramita; Yatmo, Yandi Andri (Interiority, 2024)
The understanding of interior gradually has shifted from the enclosed spatiality defined by physical boundaries to the extended notion of interiority as a dynamic condition. Understanding interior becomes more complex as dynamic conditions make it possible for interior to extend across boundaries, time, scales and typologies. This issue of Interiority presents various inquiries on the emergence of interiority and interior conditions across different scales. The articles demonstrate a wide range of perspectives on interior beyond the conventional notion of interior scale and typology, mainly addressing the domestic environment and its dynamic variants and elements. These cases acknowledge the dynamic aspects of interior architecture, which opens possibilities for various interpretations of interior, locating it within a broader understanding of social, political and cultural contexts. The emergence of interior conditions across scales calls for multidimensional thinking and multidisciplinary approaches in interior research and practice.